"The Promise of Partnership": Indian Business, the State, and the Bombay Plan of 1944. Issue 1 (10th April 2014) - Kudaisya, Medha
<x content-type="archive" xml:space="preserve">Abstract</x> This article recounts the story of the Bombay Plan of 1944, a bold vision of economic transformation for postwar India put forth by business leaders. The Plan represented a turning point in the history of Indian business. It marked the institutionalization of a long relationship between business and nationalist leadership as well as a historic moment when business groups, for the first time, unhesitatingly aligned themselves with nationalist aspirations. Underlying the Bombay Plan was the idea of a close partnership between business and the state. Yet, within a decade, this optimism died out as the autarchic features of economic policy became increasingly pronounced in independent India. The story of the Bombay Plan provides an insight into the relations between business and state in the context of development planning in India.